Pengaruh Pembelajaran Pendidikan Jasmani Berbasis Permainan terhadap Penguasaan Gerak Dasar Siswa Kelas III Sekolah Dasar - Istiyono; agus kurniadi (STKIP Subang, 2025)
This study aims to determine the effect of game-based physical education learning on the mastery of basic movements of grade III elementary school students. The research method used is an experimental method with a one group pretest-posttest design. The subjects of the study were 30 elementary school grade students. The research instrument is in the form of a test of basic movement skills which includes locomotor movement, non-locomotor and manipulative movement. The data analysis technique used the t-test. The results of the study showed that there was a significant improvement in students' basic movement mastery after the implementation of game-based physical education learning. Thus, game-based learning has a positive effect on the mastery of basic movements of grade III elementary school students